2019
DOI: 10.20524/aog.2019.0364
|View full text |Cite
|
Sign up to set email alerts
|

Anal intraepithelial neoplasia: diagnosis, screening, and treatment

Abstract: Anal intraepithelial neoplasia (AIN) is a premalignant lesion for anal cancer. It is more commonly found in high-risk patients (e.g., human papilloma virus (HPV)/human immunodeficiency virus infections, post-organ transplantation patients, and men who have sex with men) and development is driven by HPV infection. The incidence of AIN is difficult to estimate, but is heavily skewed by preexisting conditions, particularly in high-risk populations. The diagnosis is made from cytology or biopsy during routine exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
51
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(53 citation statements)
references
References 55 publications
(58 reference statements)
1
51
1
Order By: Relevance
“…The incidence of anal cancer has been increasing in high-income countries 8 , with particularly rapid increases in men who have sex with men (MSM) where the incidence is 40/100,000 in HIV-negative MSM and over 100/100,000 in HIV-positive MSM 9 , in comparison to a background rate of 2/100,000 in the general population 10 . Current treatment options for anal dysplasia include mechanical or chemical ablative techniques, but there are high recurrence rates regardless of clinical approach and it has not been formally demonstrated that any of these approaches prevents the subsequent development of cancer 11 , 12 . Moreover, recent evidence shows that the clearance of anal dysplasia in the absence of any intervention occurs at a fairly high rate of 22/100 person-years, further adding to the complexity of this clinical issue 13 .…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of anal cancer has been increasing in high-income countries 8 , with particularly rapid increases in men who have sex with men (MSM) where the incidence is 40/100,000 in HIV-negative MSM and over 100/100,000 in HIV-positive MSM 9 , in comparison to a background rate of 2/100,000 in the general population 10 . Current treatment options for anal dysplasia include mechanical or chemical ablative techniques, but there are high recurrence rates regardless of clinical approach and it has not been formally demonstrated that any of these approaches prevents the subsequent development of cancer 11 , 12 . Moreover, recent evidence shows that the clearance of anal dysplasia in the absence of any intervention occurs at a fairly high rate of 22/100 person-years, further adding to the complexity of this clinical issue 13 .…”
Section: Introductionmentioning
confidence: 99%
“…The surgical option was also effective in a large proportion of our patients, although some needed retreatment due to recurrence or incomplete excision. No cases of permanent stenosis or fecal incontinence were observed in the surgical group; however, surgery is not currently recommended due to its adverse effects, especially in patients with large lesions [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…It remains controversial whether the treatment of high-grade anal intraepithelial lesions (HSILs) prevents the subsequent development of ASCC [ 9 ], and no standard approach has been established, so that treatments vary among centers according to their resources and experience. Therapeutic options include local topical treatments with trichloroacetic acid, imiquimod, or 5-fluoruracil and more invasive treatments such as excision, fulguration, or laser therapy [ 9 ]. Surgical excision used to be a treatment of choice but is associated with adverse effects, including anal stenosis, and with recurrences and incomplete resection, especially when the anal disease is extensive [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among these, HPV 16 is the most frequent type and is considered a crucial factor for the development of squamous cell carcinoma [ 5 ]. Anal intraepithelial neoplasia and anal squamous intraepithelial lesions are considered premalignant signs of anal squamous cell carcinoma, which is driven by HPV infection [ 6 ]. Another risk factor is immunosuppression caused by acquired immune deficiency syndrome caused by human immunodeficiency virus (HIV) infection [ 7 ].…”
Section: Introductionmentioning
confidence: 99%